S?RAH LITERATURE: IN AL-ANDALUS - Kara, Şenay (Akademik Perspektif Derneği, 2025)
Andalusian S?rah Literature emerges as a significant field shaped by the intellectual and cultural environment of al-Andalus, focusing on works detailing the life and traditions of Prophet Muhammad since the early periods of Islam. This body of literature makes distinctive contributions to the broader tradition of S?rah writing within the Islamic world. The political and social structure of al-Andalus plays a pivotal role in influencing the development of these literary works, enriching them with unique local characteristics. As a result, Andalusian S?rah Literature has established a unique position within the general tradition of Islamic S?rah writing, leaving behind a rich intellectual and cultural legacy.

Endülüs Siyer Edebiyatı, İslam’ın erken dönemlerinden itibaren Hz. Muhammed’in hayatı ve sünnetiyle ilgili yazılmış eserlerin Endülüs’teki entelektüel ve kültürel ortamın etkisiyle şekillendiği bir alan olarak dikkat çekmektedir. Bu coğrafyada siyer edebiyatı, İslam dünyasının genel siyer yazım geleneğine özgün katkılarda bulunmaktadır. Endülüs’teki siyasi ve toplumsal yapı, bu tür yazınsal eserlerin gelişimini etkilemekte ve siyer edebiyatı, yerel özelliklerle zenginleşerek İslam dünyasındaki genel siyer yazım geleneği içinde kendine özgü bir yer edinip, entelektüel ve kültürel açıdan zengin bir miras bırakmaktadır.
SİYER EDEBİYATI: ENDÜLÜS
Keywords: Islamic Studies (Other); İslam Araştırmaları (Diğer)